Teachers’ Attitudes toward the Use Of L1 In EFL Classrooms - Suhayati, Lisa (CV. Pena Persada, 2019)
The discussion whether the use of mother tongue (L1) in English classrooms can help students to get a better understanding or not is still hot issues up to present days, especially in teachers’ sight. Thus, this study was aimed to determine the attitudes and beliefs of teachers regarding the use of L1 being used in teaching English as EFL and describe the functions for which L1 was employed by the teachers. The participants of this study were around 15 teachers who are teaching in several schools around Banten, West Java and Jakarta (Indonesia). To collect data, the writer conducted Likert-scale survey and semi-structured interviews with the teachers. The results showed that even though there were few of them were in doubt whether the use of L1 might negatively affect students’ English learning or not, but mainly their attitudes are positive toward the use of L1 in English classrooms. The results also indicated that the teachers employed L1 in classrooms as a teaching tool and for classroom management in order to maximize the learning outcomes.